The impact of social media on print design and distribution - Azarenkov, V. I.; Kuznetsov, E. A. (ТОВ «Друкарня Мадрид», 2024)
This article explores the influence of social media on the aesthetics and dissemination of printed materials, addressing aspects suc as visual trends, brief message formats, integration of QR codes, and augmented reality. It also examines audience growth through social media and underscores their significant role in shaping the design and distribution of printed materials.
Keywords: social media; design